Swedish modernism : architecture, consumption and the welfare state (London : Black Dog Publishing., 2010)
Swedish Modernism is a comprehensive reader analysing the role of modern architecture, city planning and consumption in the construction of the Swedish welfare state. The book draws mainly from the formative phase of the Swedish model, but also on European and American examples, and attempts to highlight the contradictions and complexities of the process of modernisation. Swedish Modernism provides an in-depth, multilayered account of the process of modernisation; whilst also highlighting the difficulties found. The debate is enriched from a diverse range of contributors including architects, researchers and leading academics from across the globe. Swedish Modernism includes an introduction from Helena Mattsson and Sven-Olov Wallenstein and contributions from leading academics from New York's Columbia University and London's UCL; alongside architects in the field. The essays explore the construction of the welfare state, contextualising this in relation to the political and social factors of the time, consumers and spectacles--from housing to national marketing programmes. Specific case studies are featured and the reader ends with a section dealing with the more general problem of historiography.
Keywords: Welfare state; Architecture and society